Buying interest on the Tiket.Com Application: Brand Image Influence Study - Maryam Farah Nur Fadhilah; Muhda Zahroh Vania; Navika Apri Alifia; Zulfa Fahmy; Khairani Zikrinawati (Experimental Student Experiences, 2024)
The research conducted by this researcher aims to show the effect of brand image on the intention to purchase tickets on the Tiket.com application. This study uses a quantitative approach. The research population is the consumers or potential consumers of Tiket.com. Sampling was carried out using purposive sampling technique and obtained as many as 100 samples. The analytical tool used is IBM SPSS Statistics 25. The analytical method used in this study is a simple linear regression analysis test. In the regression analysis, the results of the brand image regression coefficient were 0.809 with a significance of 0.000, which means sig.(p) < 0.05, it was stated that there was a significant influence on the brand image variable on the interest in buying tickets on the Tiket.com application. The results of the study show that brand image has an effect on purchase intention. In the results of the calculation of the coefficient of determination test (R square) a value of 0.643 is obtained, indicating that brand image has a positive and significant effect on purchase intention. The magnitude of the influence of brand image on consumer buying interest partially is 64.3%.